Analisis Jaringan Komunikasi German Digital #PERCUMALAPORPOLISI di Twitter - Eric Christian Lumban Tobing; Irwan Dwi Arianto (Jurnal Nomosleca, 2022)
In the early of October 2021, the Indonesian people were busy discussing the performance of the Indonesian National Police (POLRI) through the hashtag #percumalaporpolisi on Twitter social media. The hashtag is a form of digital movement from Twitter netizens about the lack of performance of the POLRI. Users interact with each other through these hashtags to form a communication network. This study analyzes quantitatively the communication network formed through #percumalaporpolisi on Twitter. This study uses communication network theory by Barry Wellman and analyzed using communication network analysis techniques based on Big Data. This hashtag was analyzed using communication network analysis techniques through three levels, namely network level, behavior level, and content level. The devices used in this research are Gephi and Rstudio applications. This study aimed to see how the networks were formed and how the analysis is on each level. Keywords: Big Data, Twitter, Communication Network Analysis, Gephi